Regional disparities and dynamic adaptation in the forest health-based industry and ecological environment: A case study of Fujian Province, China - Wenyu Chen; Shuhan Yu; Xuwang Jiang; Liyu Zhan (Ecological Indicators)
This paper provides insights into their high-quality development and sustainability by examining the adaptability of the forest health-based industry and the ecological environment. A comprehensive evaluation index system was developed, incorporating two subsystems—the forest health-based industry and the ecological environment—across three dimensions: pressure, state, and response. To conduct the analysis, we utilized various analytical tools, such as the entropy-weighted TOPSIS method, an adaptability evaluation model, standard deviation ellipses, and geographical detectors. This study examined the temporal and spatial evolution of the adaptability of the forest health-based industry and ecological environment in Fujian Province from 2013 to 2023. Key findings are as follows: (1) Fuzhou, Ningde, and Quanzhou have higher adaptability indices, indicating a more harmonious development between the forest health-based industry and the ecological environment. In contrast, regions like Nanping and Xiamen show lower indices, suggesting a need for greater policy support and resource allocation to improve adaptability. (2)The adaptability index’s spatial distribution and migration patterns reveal cyclical spatial dispersion changes from 2013 to 2023, closely associated with economic development strategies, environmental protection policies, and climate change. (3) A spatial cluster analysis of the adaptability index reveals significant shifts in adaptability levels across most regions, especially between 2015 and 2018, reflecting the complex dynamics of ecological adaptability. (4) Sanming City and Fuzhou District demonstrate effective coordination between the forest health-based industry and the ecological environment. In contrast, Zhangzhou and Nanping face more significant challenges that require attention and improvement. Lower levels mark the adaptability pattern in peripheral areas. In summary, this study underscores the importance of tailored regional strategies to enhance the adaptability and sustainable development of the forest health-based industry and ecological environment in Fujian Province, advocating for targeted policy interventions to address disparities across different areas.